A Taxonomy Approach to Studying How Gamers Review Games. (June 2017) - Koehler, Matthew J.; Arnold, Brian; Greenhalgh, Spencer P.; Boltz, Liz Owens
Background . Player-generated reviews ofvideo games represent a large, rich, and under-explored source of data for exploring what makes for an effective game. Aim . We explore whether existing theory, in the form of a comprehensive gamingtaxonomy, suitably captures the issues that players raise when they review games. Method . User-submittedgame reviews were coded along the dimensions of the comprehensive gamingtaxonomy to test the frequency of usage of each dimension. Results . We found some support for the use of thetaxonomy, as four of ninetaxonomy features were frequently present ingame reviews . We also found support for other features of reviews not encapsulated by the Bedwell et al. (2012)taxonomy . Specifically, we found that players often reviewedvideo games : a) holistically; b) by comparing them to other games, game franchises, and other reviews; and c) by judging the value of games in terms of time, money, and effort. These results have implications for usinggame reviews for future research.